Acoustic Trauma Changes the Parvalbumin-Positive Neurons in Rat Auditory Cortex - Congli Liu; Tao Xu; Xiaopeng Liu; Yina Huang; Haitao Wang; Bin Luo; Jingwu Sun (Neural Plasticity)
Acoustic trauma is being reported to damage the auditory periphery and central system, and the compromised cortical inhibition is involved in auditory disorders, such as hyperacusis and tinnitus. Parvalbumin-containing neurons (PV neurons), a subset of GABAergic neurons, greatly shape and synchronize neural network activities. However, the change of PV neurons following acoustic trauma remains to be elucidated. The present study investigated how auditory cortical PV neurons change following unilateral 1 hour noise exposure (left ear, one octave band noise centered at 16 kHz, 116 dB SPL). Noise exposure elevated the auditory brainstem response threshold of the exposed ear when examined 7 days later. More detectable PV neurons were observed in both sides of the auditory cortex of noise-exposed rats when compared to control. The detectable PV neurons of the left auditory cortex (ipsilateral to the exposed ear) to noise exposure outnumbered those of the right auditory cortex (contralateral to the exposed ear). Quantification of Western blotted bands revealed higher expression level of PV protein in the left cortex. These findings of more active PV neurons in noise-exposed rats suggested that a compensatory mechanism might be initiated to maintain a stable state of the brain.